\begin{aligned}

&\dfrac{4 x+5 y}{3}=\dfrac{x-3 y}{2}+4 / .6 \\

&\dfrac{3 x+y}{2}=\dfrac{2 x+7 y}{3}-1 / .6 \\

&\hline \hline 2(4 x+5 y)=3(x-3 y)+24 \\

&\underline{3(3 x+y)=2(2 x+7 y)-6} \\

&\hline \hline 8 x+10 y=3 x-9 y+24 \\

&9 x+3 y=4 x+14 y-6 \\

&5 x+19 y=24 \\

&5 x-11 y=-6

\end{aligned}

\begin{aligned}

&5 x+19 y-(5 x-11 y)=24-(-6) \\

&5 x+19 y-5 x+11 y=24+6 \\

&30 y=30 \\

&\underline{=} \begin{array}{l}

y=1 \\

5 x+19 y=24 \\

5 x+19=24 \\

5 x=24-19=5 \\

x=1

\end{array}

\end{aligned}